High femoral neck bone mass and density in master tennis players - Sanchis Moysi, J.; Garcia Dorado, C.; Calbet, J. A. L. (2000)
Tennis imposes a high mechanical load on the axial skeleton and the limbs. Adaptive changes result, leading to a marked increase in the muscle and bone mass of the dominant arm. The lower limbs are stressed too, mainly by sudden acceleration, fast changes in the direction of a displacement and occasionally, by jumps. These forces might act on the femoral neck and could presumably lead to an increase in femoral neck bone mass and bone mineral density, which could help to prevent osteoporotic fractures later in life. The aim of this study was to determine the effects of life-time tennis participation on femoral bone mineral content (BMC) and density (BMD) in elite tennis players. Femoral BMC and BMD were assessed by dual energy X-ray examinations (DXA: Hologic QDR-1500) in 17 male tennis players and 15 male sedentary subjects from the same population. The mean participation in tennis was 32±12 years, and the mean time devoted to training and playing 7.4±11 hours per week (range 2-10 hours per week). Leg maximal extension strength was similar in both groups, as was the amount of fat mass and lean mass in the legs. However, the tennis players showed 16% more BMC (1182±132 and 1018±167 g, p< 0.01) and 10% higher BMD (1.42±0.08 and 1.29±0.1g.cm-2, p<0.01) in the legs. Higher BMC was observed at the femoral neck sub-regions, at the femoral neck, the greater trochanter, inter-trochanteric area and Wards triangle. BMD was also higher in the femoral sub-regions of the tennis players. The researchers conclude that life-time tennis participation is associated with 15-30% higher levels of both BMC and BMD at the clinically-relevant femoral neck areas in middle-aged men. This suggests that tennis could be recommended as an osteotrophic exercise, to prevent osteoporosis later in life.